Special issue call for papers: Thirty years of affective events theory: New directions in the knowledge era - Rueff-Lopes, R.; Cropanzano, R.; Navarro, J.; Junça Silva, A. (European Journal of Work and Organizational Psychology, 2026)
We are honoured to have Professor Russell Cropanzano serve as Honorary Guest Editor for this special issue. Professor Cropanzano is one of the original authors of Affective Events Theory (AET) and a leading figure in the study of emotions, justice, and well-being at work. His involvement in this special issue represents a unique opportunity to both honour the theory’s intellectual origins and advance its development in light of contemporary work contexts. The participation of Professor Cropanzano underscores the special issue’s commitment to theoretical rigour, historical continuity, and forward-looking innovation in affective science.